Pengembangan Tes Kognitif Higher Order Thinking Skills Muatan Pelajaran IPA Kelas V Sekolah Dasar - Joyce Angela; Suparjan Suparjan; Rio Pranata; Siti Halidjah; Asmayani Salimi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to develop the higher-order thinking skills questions in thematic learning for grade V of State Elementary School 34 Pontianak Selatan. This research and development used Borg & Gall’s development model consisting of research and information gathering, planning, development of the initial product, initial field trials, main product revisions, field trials, and operational product revisions. Data were obtained from 10 students in Grade V D and 32 students in Grade V C. The data collection instruments were interview guidelines, questionnaires, and tests in the form of HOTS questions. Data were analyzed using the feasibility analysis of HOTS questions in terms of material, construction, and language aspects as well as item analysis. The results showed that the HOTS questions consisted of 20 multiple choice questions, feasibility in terms of the construction aspect obtained a percentage of 96.6% with very good criteria, the material aspect was 85% with very good criteria, the language aspect was 93.3% with very good criteria. so that the HOTS test product is declared feasible for use in the learning process. As for the research results, the validity level of 20 HOTS-based questions is in the valid category, the degree of reliability is 0.855 (high). Based on the discriminating power and level of difficulty of the 20 items, there are 19 items that match HOTS characteristics.